Morphological Notes on the Worker and Queen Larvae of the Thief Ant Solenopsis helena (Hymenoptera, Formicidae, Myrmicinae) from Brazil - Paterson Fox, Eduardo Goncalves; Solis, Daniel Russ [UNESP]; Rossi, Monica Lanzoni; Mackay, William; Pacheco, Jose (Florida Entomological Soc, 2011)
Young and mature larvae of queen and workers of the thief ant, Solenopsis helena, are herein described for the first time. Specimens were treated and described by usual methods of light and scanning electron microscopy. Many of the observed characteristics confirmed traits of the thief ant larva, reinforcing the assumption that they are a distinct group from fire ants. The larva of S. helena can be recognized from other close species by details of the mouthparts, but seem extensively similar to Solenopsis molesta. These findings are useful for taxonomic studies and phylogenetic inferences.

Larvas de diferentes tamanhos de operarias e rainhas de Solenopsis helena são descritas. Os espécimes coletados em São Paulo, Brasil, foram medidos e descritos por meios convencionais de microscopia ótica e eletrônica de varredura. As larvas desta espécie diferem de outras espécies próximas por detalhes das peças bucais, mas parecem ser muito semelhantes a descrições anteriores de Solenopsis molesta. Muitos caracteres distintos de larvas das formigas do antigo subgênero Diplorohptrum foram aqui confirmados, sugerindo que realmente são um grupo distinto de formigas dentro do gênero Solenopsis. Estas informações são uteis em estudos maiores de filogenia e taxonomia do grupo.
Keywords: Larval description; taxonomy; Solenopsidini; scanning electron microscopy; ant morphology